2011
DOI: 10.1002/dneu.20859
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization within neurites: Its mechanisms and implications

Abstract: Neurons are morphologically characterized by long processes extending from a cell body. These processes, the dendrites and axon, are major sub-cellular compartments defined by morphological, molecular, and functional differences. However, evidence from vertebrates and invertebrates suggests that, based on molecular distribution, individual axons and dendrites are further divided into distinct compartments; many membrane molecules involved in axon guidance and synapse formation are localized to specific segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…For example, the microtubule cytoskeleton is organized differently in axons and dendrites, allowing distinct modes of trafficking (Baas et al, 1988;Horton and Ehlers, 2003). Beyond this basic level of compartmentalization, neurons display extreme diversity in axon and dendrite morphology, and both axons and dendrites contain structurally and functionally distinct subdomains (Katsuki et al, 2011;Masland, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the microtubule cytoskeleton is organized differently in axons and dendrites, allowing distinct modes of trafficking (Baas et al, 1988;Horton and Ehlers, 2003). Beyond this basic level of compartmentalization, neurons display extreme diversity in axon and dendrite morphology, and both axons and dendrites contain structurally and functionally distinct subdomains (Katsuki et al, 2011;Masland, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…RhoA activation may be restricted to the rear via the observed asymmetric flow; although in contrast Rac1, which moved equally well in all directions, is likely activated locally via spatial control of upstream signals. Previous work has suggested that actin and other cytoskeletal components form barriers to diffusion and accelerate cross-cell transport by restricting trafficking to particular pathways (11). pCF/ FLIM makes these pathways visible and will enable us to correlate localized activation with directed movement through specific subcellular regions.…”
Section: Discussionmentioning
confidence: 99%
“…). These findings raise intriguing questions on the development, maintenance, and function of these sub‐compartments (Katsuki et al, ).…”
Section: Introduction: Sub‐compartments In Neuronsmentioning
confidence: 99%